2018
DOI: 10.3390/medicines5030062
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Age, Comorbidities and Use of Radiotherapy in Women with Breast Cancer: Implications for Survival

Abstract: Background: Radiotherapy (RT) plays an important role in the management and survival of patients with breast cancer. The aim of this study was to examine the association between age, comorbidities and use of RT in this population. Methods: Patients diagnosed with breast cancer from 2004–2013 were identified from the American College of Surgeons National Cancer Database (NCDB). Follow-up time was measured from the date of diagnosis (baseline) to the date of death or censoring. Adjusted hazard ratios (aHR) and 9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…There were 67.5–89% of patients still receipt of adjuvant RT after the Cancer and Leukemia Group B (CALGB) 9343 publication (5, 6), which was similar to our study. In addition, we found that receipt of postoperative RT improved BCSS compared with patients who did not have postoperative RT, data that are similar to results from two National Cancer Database (NCDB) studies (21, 22). Therefore, elderly patients for whom postoperative RT can be omitted safely should be investigated further.…”
Section: Discussionsupporting
confidence: 83%
“…There were 67.5–89% of patients still receipt of adjuvant RT after the Cancer and Leukemia Group B (CALGB) 9343 publication (5, 6), which was similar to our study. In addition, we found that receipt of postoperative RT improved BCSS compared with patients who did not have postoperative RT, data that are similar to results from two National Cancer Database (NCDB) studies (21, 22). Therefore, elderly patients for whom postoperative RT can be omitted safely should be investigated further.…”
Section: Discussionsupporting
confidence: 83%
“…A recent study from nine European countries suggested that elderly patients should receive standard medical treatment whenever possible to maximize the benefits of modern evidence-based treatments [ 23 ]. Given the increased burden of comorbidities [ 24 ], frailty among elderly patients could lead to therapy delays or refusals, which might lead to lower survival rates [ 25 , 26 ]. In this study, only 20% of deaths were from BC, while cardiovascular, cerebrovascular, and lung diseases were common causes of death in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…The NCDB database has been previously described [37,38]. In brief, over 1500 Commission on Cancer (CoC) accredited cancer programs in the United States (US) report data to the NCDB, encompassing approximately 70% of incident cancer cases [39].…”
Section: Methodsmentioning
confidence: 99%